The F-Box Protein CG5003 Regulates Axon Pruning and the Integrity of the Drosophila Mushroom Body - Yang, Mengying; Guo, Yige; Wang, Shuran; Chen, Changyan; Chang, Yung-Heng; Ho, Margaret Su-chun (Frontiers in Molecular Neuroscience, 2021)
Protein homeostasis serves as an important step in regulating diverse cellular processes underlying the function and development of the nervous system. In particular, the ubiquitination proteasome system (UPS), a universal pathway mediating protein degradation, contributes to the development of numerous synaptic structures, including the Drosophila olfactory-associative learning center Mushroom Body (MB), thereby affecting associated function. Here we describe the function of a newly characterized Drosophila F-box protein CG5003, an adaptor for the RING-domain type E3 ligase (SCF complex), in MB development. Lacking CG5003 ubiquitously causes MB gamma axon pruning defects, and selective CG5003 expression in pan-neurons leads to a/b lobe abnormalities. Interestingly, change in CG5003 expression in MB neurons does not cause any abnormalities in axons, suggesting a non-cell-autonomous role of CG5003. Mass spectrum analysis indicates that silencing CG5003 expression in all neurons affects expression levels of proteins in cell and structural morphogenesis, transcription regulator activity, and catalytic activity. Our findings reinforce the importance of UPS and identify a new factor in regulating neuronal development as exemplified by the synaptic structure MB.